Construction of an endoplasmic reticulum stress-related gene model for predicting prognosis and immune features in kidney renal clear cell carcinoma - Shen, Yuanhao; Cao, Yinghao; Zhou, Lei; Wu, Jianfeng; Mao, Min (Frontiers in Molecular Biosciences, 2022)
Background: Kidney renal clear cell carcinoma (KIRC) is one of the most lethal malignant tumors with a propensity for poor prognosis and difficult treatment. Endoplasmic reticulum (ER) stress served as a pivotal role in the progression of tumor. However, the implications of ER stress on the clinical outcome and immune features for KIRC patients still need elucidation. Methods: We identified differentially expressed ER stress-related genes between KIRC specimens and normal specimens with the TCGA dataset. Then we explored biological function and genetic mutation of ER Stress-related differentially expressed genes (DEGs) by multiple bioinformatic analysis. Subsequently, LASSO analysis and univariate Cox regression analysis were applied to construct a novel prognostic model based on ER stress-related DEGs. Next, we confirmed its predictive performance of this model with GEO dataset and explored the potential biological functions by functional enrichment analysis. Finally, KIRC patients stratified by the prognostic model were assessed for tumor microenvironment (TME), immune infiltration and immune checkpoints through single sample Gene Set Enrichment Analysis (ssGSEA) and ESTIMATE analysis. Results: we constructed a novel prognostic model, including eight ER stress-related DEGs, which could stratify two risk groups in KIRC. The prognostic model and a model-based nomogram could accurately predict the prognosis of KIRC patients. Functional enrichment analysis indicated several biological functions related to the progression of KIRC. The high-risk group showed higher levels of tumor infiltration by immune cells and higher immune scores. Conclusion: In this study, we constructed a novel prognostic model based on eight ER stress-related genes for KIRC patients, which would help to predict the prognosis of KIRC and provide a new orientation to further researches on personalized immunotherapy in KIRC.